THE EFFECTIVENESS OF CROSSWORD PUZZLES WITH VARIED CLUES TYPES ON VOCABULARY MASTERY AMONG SECONDARY SCHOOL STUDENTS IN JEMBER - Anisa Intama; Kristi Nuraini; Muhlisin Rasuki (Premise: Journal of English Education and Applied Linguistics, 2026)
This study examines the effectiveness of crossword puzzles that integrate various types of clues in improving vocabulary mastery among secondary school students in an EFL learning environment. Vocabulary learning in the classroom can be challenging, as students have limited opportunities to interact with English. On the other hand, empirical research focusing on teaching strategies with structured instructional support is also limited. Therefore, this study aims to examine whether the use of crossword puzzles integrating varied clue types can support vocabulary learning. This study employed a pre-experimental one group pretest-posttest design, supported by qualitative data collected through questionnaires. Because the distribution of vocabulary test scores did not show a normal distribution, non-parametric analysis was performed. Qualitative findings indicate that clues integrated into crossword puzzles support students, including definitions, synonyms, antonyms, fill-in-the-blanks, and pictures with the help of letter clues in each grid, which help students recall the target vocabulary they have learned, in turn increases their confidence during the activity. The results of the study indicate that crossword puzzles with varied clue types showed improvements in students vocabulary development and engagement of the learning activity in a rural EFL classroom. Practically, the findings suggest that teachers may adapt crossword puzzles with varied clue types as a low-cost and accessible strategy to support vocabulary learning in contexts where exposure to English and instructional resources are limited.